COGNITIVE LEARNING THEORY IN THE PERSPECTIVE OF ISLAMIC EDUCATION - Thayyibi, Muhammad Ilham; Ratnasari, Dwi (Pascasarjana Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga, 2022)
Cognitive theory is classified as a theory that plays an important role in the development of educational theory, but there are still few educational practitioners who understand the concept of cognitive theory. At the beginning of the 15th century H , Muslim scientists strengthened the spirit to return to Islamic teachings based on the Al-Quran and Hadith. So it is not impossible if modern learning theories exist in the Qur'an and Hadith, or at least find their equivalent. So that western concepts can be juxtaposed with concepts based on the Qur'an and Hadith . The purpose of this study is to dissect the actual concept of cognitive learning theory in the perspective of Islamic education . The method used is library research , namely library research by collecting literature that talks about cognitive learning theory and Islamic education. The result of the research is that the cognitive theory of Islamic education perspective focuses on the ability to think, should pay attention to the physical and psychological development of students, focus their attention on the process of transmitting knowledge and educators play a very important role in the cognitive growth of students.